Rancang Bangun Sistem Pembeda Gerakan Berlari dan Berjalan Untuk Atlet Lari Menggunakan MPU6050 dan Metode Klasifikasi K-Nearest Neighbor - Agastya Bramanta Sanjaya; Dahnial Syauqy; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Athletics run is one of sport as archievment. In developing the ability of athletes needs training. Training in athletics running athletes requires at least 2 main components, coaches and athletes. Often the athlete does not do training properly and the trainer does not pay attention to it, this may lead training not getting maximum results. From the problem was create a system that can classify the movement of running, walking and stopping using MPU6050 sensor module with the input are sensor values from gyroscope and accelerometer with method k-nearest neighbor as classification algorithm. This system expected to can help the coaches to monitor the exercise of an athlete by not having to always observe the athlete during exercise and this system is expected can help too coaches conduct training with the number of athletes running more than 1 person in sametime. This system is based on the wearable device used on the athlete's body and sends sensor data to other devices on the trainer. The system has an accuracy rate of 96.7% in distinguishing running, running and silent movements as well as the required compute time of 0.922 seconds.